Governança democrática: por uma nova perspectiva de análise e construção das políticas de segurança pública no Brasil - Ballesteros, Paula K. Rodriguez (2012)
This dissertation is dedicated to making a review of the literature on democratic governance, seeking to contribute to new conceptual analysis of the management of public security policies. It is presenting a new perspective to analyze what and how policies have been developed for public safety in order to overcome the problem of violence and crime in accordance with its magnitude and complexity. To this end, the paper highlights the role of government in the task of governance, discussing the exercise of the legitimate monopoly of force from the perspective of participation and inclusion of new actors, the relationship between agencies and spheres of power, the construction of new patterns of authority and legitimacy, and the integrated management of public policies in a democratic environment. The literature on democratic governance has the potential to provide insight to this analysis, since it combines the political approach to the administrative perspective, adding to the general guidelines on State action indications of formulation, monitoring and evaluation criteria of public policies in a society more dynamic and multifaceted, whose pressing demands arise as a challenge to contemporary governments.